Hybrid methods for lot sizing on parallel machines - Fiorotto, Diego Jacinto [UNESP]; Araujo, Silvio Alexandre de [UNESP]; Jans, Raf (Elsevier, 2015)
We consider the capacitated lot sizing problem with multiple items, setup time and unrelated parallel machines, and apply Dantzig–Wolfe decomposition to a strong reformulation of the problem. Unlike in the traditional approach where the linking constraints are the capacity constraints, we use the flow constraints, i.e. the demand constraints, as linking constraints. The aim of this approach is to obtain high quality lower bounds. We solve the master problem applying two solution methods that combine Lagrangian relaxation and Dantzig–Wolfe decomposition in a hybrid form. A primal heuristic, based on transfers of production quantities, is used to generate feasible solutions. Computational experiments using data sets from the literature are presented and show that the hybrid methods produce lower bounds of excellent quality and competitive upper bounds, when compared with the bounds produced by other methods from the literature and by a high-performance MIP software.
Keywords: Lot sizing; Parallel machines; Reformulation; Hybrid methods; Dantzig–Wolfe decomposition; Lagrangian relaxation; Problema de dimensionamento de lotes; Relaxação lagrangiana; Geração de colunas